COP1 destabilizes DELLA proteins in Arabidopsis - Blanco Touriñán, Noel (2020)
DELLA transcriptional regulators are central components in the control of plant growth responses to the environment. This control is considered to be mediated by changes in the metabolism of the hormones gibberellins (GAs), which promote the degradation of DELLAs. However, here we show that warm temperature or shade reduced the stability of a GA-insensitive DELLA allele in Arabidopsis thaliana. Furthermore, the degradation of DELLA induced by the warmth preceded changes in GA levels and depended on the E3 ubiquitin ligase CONSTITUTIVELY PHOTOMORPHOGENIC1 (COP1). COP1 enhanced the degradation of normal and GAinsensitive DELLA alleles when coexpressed in Nicotiana benthamiana. DELLA proteins physically interacted with COP1 in yeast, mammalian, and plant cells. This interaction was enhanced by the COP1 complex partner SUPRESSOR OF phyA-105 1 (SPA1). The level of ubiquitination of DELLA was enhanced by COP1 and COP1 ubiquitinated DELLA proteins in vitro. We propose that DELLAs are destabilized not only by the canonical GA-dependent pathway but also by COP1 and that this control is relevant for growth responses to shade and warm temperature.